2015
DOI: 10.1016/j.jaci.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Eosinophilic Esophagitis Symptom Scores (PEESS v2.0) identify histologic and molecular correlates of the key clinical features of disease

Abstract: Background The Pediatric Eosinophilic Esophagitis Symptom Score (PEESS® v2.0) measures patient-relevant outcomes. However, whether patient-identified domains (dysphagia, gastrointestinal reflux disease (GERD), nausea/vomiting, and pain) align with clinical symptomology and histopathologic and molecular features of eosinophilic esophagitis (EoE) is unclear. Objective The purpose of this study was to determine if clinical features of EoE, measured through the PEESS® v2.0, associate with histopathologic and mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
115
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 53 publications
0
115
0
6
Order By: Relevance
“…The current disease monitoring standard dictates that all patients undergo invasive endoscopy with tissue biopsies due to poor correlation between clinical symptoms and tissue inflammation [10]. Any reduction of invasive procedures through the use of less-invasive blood biomarkers would be valuable.…”
Section: To the Editormentioning
confidence: 99%
“…The current disease monitoring standard dictates that all patients undergo invasive endoscopy with tissue biopsies due to poor correlation between clinical symptoms and tissue inflammation [10]. Any reduction of invasive procedures through the use of less-invasive blood biomarkers would be valuable.…”
Section: To the Editormentioning
confidence: 99%
“…Here, we focused on uncovering the mechanism of allergic inflammation in eosinophilic esophagitis (EoE), a chronic, food-driven, inflammatory allergic disease of the esophagus ( 3 ). EoE is diagnosed according to the number of infiltrating eosinophils in the esophageal squamous epithelium, but other associated inflammatory cells are likely involved including mast cells, basophils, and lymphocytes ( 46 ). Besides being a recently emerging allergic disease that is in need of deeper understanding, EoE provides a unique opportunity to probe human allergic inflammation at the tissue level, as the diseased tissue is readily available for experimental investigation by routine endoscopic biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…Eosinophilic Eosophagitis (EoE) is a chronic inflammatory disorder of the esophagus, seen in both children and adults, and is 3–4 times more common in males than females [2]. Diagnosis of EoE has relied on quantification of eosophageal eosinophils by biopsy and patient-reported symptoms but recent studies have supported the use of tissue-based molecular biomarker assessment, based on gene expression signatures [3], aiding patient diagnosis [4]. Strong correlations between gene expression profiles and symptoms were found, particularly dysphagia [4].…”
mentioning
confidence: 99%
“…Diagnosis of EoE has relied on quantification of eosophageal eosinophils by biopsy and patient-reported symptoms but recent studies have supported the use of tissue-based molecular biomarker assessment, based on gene expression signatures [3], aiding patient diagnosis [4]. Strong correlations between gene expression profiles and symptoms were found, particularly dysphagia [4]. Early work looking at the EoE-associated transcriptional profile concluded that there were no differences between males and females [5] but this was performed in childhood EoE and recent studies have demonstrated that gender significantly influences the clinical presentation of adult EoE, particularly dysphagia [68].…”
mentioning
confidence: 99%